2021
DOI: 10.1128/jcm.02314-20
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/XDR: a 10-Color Reflex Assay Suitable for Point-of-Care Settings To Detect Isoniazid, Fluoroquinolone, and Second-Line-Injectable-Drug Resistance Directly from Mycobacterium tuberculosis-Positive Sputum

Abstract: We describe the design, development, analytical performance and a limited clinical evaluation of the 10-color Xpert MTB/XDR assay (CE-IVD only, not for sale in the US). This assay is intended as a reflex test to detect resistance to isoniazid (INH), fluoroquinolones (FLQ), ethionamide (ETH) and second-line injectable drugs (SLID) on unprocessed sputum samples and concentrated sputum sediments which are positive for Mycobacterium tuberculosis. The Xpert MTB/XDR assay simultaneously amplifies eight genes and pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…As the study was designed to assess the Xpert MTB/XDR assay as a reflex test to any TB positive result, 7 only Xpert MTB/RIF and Ultra M. tuberculosis -positive patients were enrolled in our study, and so no data were available to confirm Xpert MTB/XDR specificity for TB detection. Although previous studies have demonstrated the limit of detection of the Xpert MTB/XDR assay to be equivalent to Xpert MTB/RIF, 10,18 additional prospective, clinical data would be helpful to support this finding and define best use cases. Furthermore, the study was designed to evaluate a high number of drug-resistant specimens to provide accurate sensitivity estimates, and this was achieved by testing mostly RIF resistant samples, but also meant that sample size was relatively low to assess Xpert MTB/XDR specificity for INH resistance detection.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As the study was designed to assess the Xpert MTB/XDR assay as a reflex test to any TB positive result, 7 only Xpert MTB/RIF and Ultra M. tuberculosis -positive patients were enrolled in our study, and so no data were available to confirm Xpert MTB/XDR specificity for TB detection. Although previous studies have demonstrated the limit of detection of the Xpert MTB/XDR assay to be equivalent to Xpert MTB/RIF, 10,18 additional prospective, clinical data would be helpful to support this finding and define best use cases. Furthermore, the study was designed to evaluate a high number of drug-resistant specimens to provide accurate sensitivity estimates, and this was achieved by testing mostly RIF resistant samples, but also meant that sample size was relatively low to assess Xpert MTB/XDR specificity for INH resistance detection.…”
Section: Discussionmentioning
confidence: 93%
“…Upon closer examination, it was determined that 11 of the 14 false-negative results in New Delhi were from specimens that were phenotypically SLI-susceptible but heteroresistant by WGS, with rrs c1402a and g1484t mutations present in only a fraction of WGS reads at levels likely undetectable by the Xpert MTB/XDR assay (the rrs c1402a mutation was detected in <50% of reads for nine of the 11 samples). 10,18 Ultimately, the clinical relevance of these minor resistant populations is unclear given that these samples were phenotypically SLI-susceptible. If only pDST was considered as a reference standard in this study, the sensitivity of the Xpert MTB/XDR assay would improve to 67–75% for the detection of SLI resistance in New Delhi and 75–92% overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, despite the enormous success of scaling up CBNAATs, just 44% of estimated MDR cases were diagnosed in India in 2019 [ 11 ]. In July 2020, the Foundation for Innovative New Diagnostics and Cepheid, Inc., announced the launch of the new Xpert MTB/XDR cartridges, which enable expanded DR profiling against multiple drugs such as isoniazid, ethionamide, fluoroquinolones, amikacin, kanamycin, and capreomycin with a turnaround time of less than 90 minutes [ 20 ]. While such tests can greatly overcome the diagnostic limitations of existing CBNAAT systems, they are still being evaluated by the WHO, and it may take considerable time to scale them up (with consideration of a cost-benefit analysis and infrastructure) after being introduced into the Indian market.…”
Section: Limited Diagnostic Capacity For Dr-tb In Peripheral and Resource-limited Regions Of Indiamentioning
confidence: 99%
“…Xpert ® MTB/RIF Ultra and Xpert ® MTB/RIF have a similar sensitivity (94.9% vs. 95.3%, respectively) and specificity (99.1% vs. 98.8%) for detecting rifampicin resistance [61]. The recently developed Xpert ® MTB/XDR (Cepheid, Sunnyvale, CA, USA), capable of identifying 16 resistance-conferring mutations in M. tuberculosis (Table 1) [62], has been shown to have a high sensitivity (94.1-100%) and specificity (100%) for detecting resistance to isoniazid, fluoroquinolones and second-line injectable drugs; the sensitivity and specificity for detecting ethionamide resistance was slightly lower (88.5% and 97.3%, respectively) [63]. Another study has shown that the assay is capable of detecting 100% of the tested mutations for resistance to these drugs but has more variable outcomes for detecting heteroresistance [64].…”
Section: Nucleic Acid Amplification Assaysmentioning
confidence: 99%